2019
DOI: 10.3390/w11091771
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Performance of CMIP5 Global Climate Models for Simulating Future Precipitation Change in the Tibetan Plateau

Abstract: In this study, the performance of 33 Coupled Model Intercomparison Project 5 (CMIP5) global climate models (GCMs) in simulating precipitation over the Tibetan Plateau (TP) was assessed using data from 1961 to 2005 by an improved score-based method, which adopts multiple criteria to achieve a comprehensive evaluation. The future precipitation change was also estimated based on the Delta method by selecting the submultiple model ensemble (SMME) in the near-term and far future (2051-2095) periods under Represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 62 publications
1
27
0
Order By: Relevance
“…Based on a similar coupling design, Strandberg et al (2011) found that the impact of a different land cover on LGM climate simulations is small compared to the uncertainties in the proxy reconstructions. Even though this is also true in our study, our results and discussion suggest that modifications in land cover like deforestation could play an important role when other forcing agents marginally change, as is observed in some climate change scenarios such as RCP 2.6 and 4.5 (Strandberg and Kjellström, 2019;Davin et al, 2020;Jia et al, 2020).…”
Section: Influence Of External Forcing and Land Cover On Climatesupporting
confidence: 49%
See 1 more Smart Citation
“…Based on a similar coupling design, Strandberg et al (2011) found that the impact of a different land cover on LGM climate simulations is small compared to the uncertainties in the proxy reconstructions. Even though this is also true in our study, our results and discussion suggest that modifications in land cover like deforestation could play an important role when other forcing agents marginally change, as is observed in some climate change scenarios such as RCP 2.6 and 4.5 (Strandberg and Kjellström, 2019;Davin et al, 2020;Jia et al, 2020).…”
Section: Influence Of External Forcing and Land Cover On Climatesupporting
confidence: 49%
“…Global climate models (GCMs) show little agreement in LGM simulations for Europe (Braconnot et al, 2012;Kageyama et al, 2017;Ludwig et al, 2019;Kageyama et al, 2021). It has been suggested that a reason for the large uncertainty could be related to the spatial resolution in the climate models (Walsh et al, 2008;Jia et al, 2019b;Ludwig et al, 2019;Raible et al, 2020). Advances in regional climate models have led to the application of such models to the glacial climate of Europe on a high spatial resolution (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…3a-3d)] was employed to examine trends in monthly time series of the temperature datasets. This is a nonparametric statistic that has been used in earlier studies for trend analysis in climate time series data due to its robustness (Akinsanola et al, 2017;Abatan et al, 2016;Agyekum et al, 2018;Shiru et al, 2018;Jia et al, 2019;Mondal et al, 2018;Fu et al, 2013;Akande et al, 2017). The method was therefore utilized in this study to assess the trends and the magnitude of monthly time series data at 5 % significant level ( ).…”
Section: Methodsmentioning
confidence: 99%
“…For comparison purposes, the CMIP5 model data and Asfazari data were regridded to a uniform horizontal resolution 0.5 × 0.5 grid using a bilinear interpolation scheme before further processing. This technique is a resampling F I G U R E 3 The climatological area-averaged bias in (a) the annual frost days, (b) TNn, (c) TXn, (d) Tn90p, (e) Tx90p and (f) the warm spell duration index, for each model relative to the observations method that uses the distance-weighted average of the four nearest pixel values to estimate a new pixel value (Zhou and Zhao, 2015;Jia et al, 2019) which has little "smoothing" effect on extreme climatic values (Kopparla et al, 2013).…”
Section: Methodsmentioning
confidence: 99%